Model Kesejahteraan Keluarga Berasaskan Konsep Al-Falāḥ: Analisis Tematik Al-Quran Dan Kajian Literatur: A Family Well-Being Model Based on the Concept of al-Falāḥ: A Thematic Qur’anic Analysis and Literature Review - Abdul Jalil, Siti Jamiaah; Md Sham, Fariza; Ismail, A’dawiyah; Osman, Khazri; Ismail, Rozmi; Md Yusoff , Yusmini (Journal of Al-Falah, 2025)
Family well-being serves as the foundation for the quality of individuals and society. In the Islamic perspective, the concept of al-Falāḥ encompasses prosperity, success, and blessings in both worldly life and the Hereafter. This study aims to identify the elements of family well-being based on the al-Falāḥ framework through content analysis of Qur’anic verses and a comprehensive literature review. The findings reveal that al-Falāḥ-based family well-being emphasizes holistic development that balances spiritual and material needs, with taqwā (piety) as its core foundation. Five main domains were identified: spiritual (inner tranquility), economic (adequate and lawful provision), educational (intellectual competence), social (harmonious relationships), and health (physical and mental well-being). The simultaneous development of these domains not only enhances family well-being but also generates positive impacts on societal well-being.